2016
DOI: 10.1161/jaha.116.003922
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐590 Promotes Transdifferentiation of Porcine and Human Fibroblasts Toward a Cardiomyocyte‐Like Fate by Directly Repressing Specificity Protein 1

Abstract: BackgroundReprogramming of cardiac fibroblasts into induced cardiomyocyte‐like cells represents a promising potential new therapy for treating heart disease, inducing significant improvements in postinfarct ventricular function in rodent models. Because reprogramming factors effective in transdifferentiating rodent cells are not sufficient to reprogram human cells, we sought to identify reprogramming factors potentially applicable to human studies.Methods and ResultsLentivirus vectors expressing Gata4, Mef2c, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 46 publications
3
61
0
Order By: Relevance
“…Although we were able to demonstrate differences between groups despite this variability, we do not have a good explanation for this variability between groups. In this context, we would note that we assayed RNA expression at 14 days after reprogramming factor infection based upon original research in this field suggesting that cellular reprogramming occurs over several weeks, 31,32 but additional studies demonstrated similar expression patterns as early as 5 days post-infection (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Although we were able to demonstrate differences between groups despite this variability, we do not have a good explanation for this variability between groups. In this context, we would note that we assayed RNA expression at 14 days after reprogramming factor infection based upon original research in this field suggesting that cellular reprogramming occurs over several weeks, 31,32 but additional studies demonstrated similar expression patterns as early as 5 days post-infection (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MiR-590 a direct repressor of Sp1 has also been studied in conversion studies. When miR-590-mediated repression of Sp1 was done on human cardiac cells, it was found that it significantly upregulated the associated genes and promoted cardiac cellular reprogramming, showing that Sp1 may be an intermediary in this step [106] The E-Ras/JNK signalling is a critical mechanism to generate iPS cells by transduction of 4 factors. E-Ras was found to enhance binding of Sp1 on the cyclins to promote cell proliferation and reprogramming.…”
Section: Influence Of Sp1 On Cellular Reprogrammingmentioning
confidence: 99%
“…showing that Sp1 may be an intermediary in this step [106] The E-Ras/JNK signalling is a critical mechanism to generate iPS cells by transduction of 4 factors. E-Ras was found to enhance binding of Sp1 on the cyclins to promote cell proliferation and reprogramming.…”
Section: Influence Of Sp1 On Cellular Reprogrammingmentioning
confidence: 99%
“…Zhao et al used a combination of GMHT, miRNA-1, miRNA-133, miRNA-208, miRNA-499, Y-27632, and A83-01 in MEFs and mouse adult fibroblasts to achieve ~60% cardiac troponin T+ and 60% α -actinin+ iCMs [ 29 ]. miRNA-590, a miRNA that can induce adult cardiomyocyte proliferation, was recently shown to be able to replace HAND2 and MYOCD in GMT direct reprogramming experiments using human and porcine fibroblasts [ 38 , 39 ]. While GMT was initially shown to be sufficient for cardiac reprogramming, further studies have indicated that a multiprong approach may be necessary to enhance reprogramming and could hold great promise for future in vivo clinical application.…”
Section: Improving the Efficiency Of Direct Reprogramming With Biomentioning
confidence: 99%